Lessons learnt from human papillomavirus (HPV) vaccination in 45 low- and middle-income countries - Gallagher, Katherine E.; Howard, Natasha; Kabakama, Severin; Mounier-Jack, Sandra; Griffiths, Ulla K.; Feletto, Marta; Burchett, Helen E. D.; LaMontagne, D. Scott; Watson-Jones, Deborah (PLOS ONE, 2017)
Objective To synthesise lessons learnt and determinants of success from human papillomavirus (HPV) vaccine demonstration projects and national programmes in low- and middle-income countries (LAMICs). Methods Interviews were conducted with 56 key informants. A systematic literature review identified 2936 abstracts from five databases; after screening 61 full texts were included. Unpublished literature, including evaluation reports, was solicited from country representatives; 188 documents were received. A data extraction tool and interview topic guide outlining key areas of inquiry were informed by World Health Organization guidelines for new vaccine introduction. Results were synthesised thematically. Results Data were analysed from 12 national programmes and 66 demonstration projects in 46 countries. Among demonstration projects, 30 were supported by the GARDASIL® Access Program, 20 by Gavi, four by PATH and 12 by other means. School-based vaccine delivery supplemented with health facility-based delivery for out-of-school girls attained high coverage. There were limited data on facility-only strategies and little evaluation of strategies to reach out-of-school girls. Early engagement of teachers as partners in social mobilisation, consent, vaccination day coordination, follow-up of non-completers and adverse events was considered invaluable. Micro-planning using school/ facility registers most effectively enumerated target populations; other estimates proved inaccurate, leading to vaccine under- or over-estimation. Refresher training on adverse events and safe injection procedures was usually necessary. Conclusion Considerable experience in HPV vaccine delivery in LAMICs is available. Lessons are generally consistent across countries and dissemination of these could improve HPV vaccine introduction.